2016
DOI: 10.1002/jae.2555
|View full text |Cite
|
Sign up to set email alerts
|

Have Standard VARS Remained Stable Since the Crisis?

Abstract: Summary Small vector autoregressions are commonly used in macroeconomics for forecasting and evaluating shock transmission. This requires VAR parameters to be stable over the evaluation and forecast sample or modeled as time‐varying. Prior work has considered whether there were sizable parameter changes in the early 1980s and in the subsequent period until the beginning of the new century. This paper conducts a similar analysis focused on the period since the recent crisis. Using a range of techniques, we prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 68 publications
(74 reference statements)
2
30
0
Order By: Relevance
“…and covariance matrix in out-of-sample forecasting, our results bear some resemblance to those of Aastveit et al (2017).…”
Section: Out-of-sample Forecastssupporting
confidence: 73%
See 1 more Smart Citation
“…and covariance matrix in out-of-sample forecasting, our results bear some resemblance to those of Aastveit et al (2017).…”
Section: Out-of-sample Forecastssupporting
confidence: 73%
“…29 Finding that the model with time-varying parameters and stochastic volatility has difficulties outperforming the model with constant parameters Footnote 27 continued was that a model with drifting parameters and stochastic volatility could generate improvements in forecast accuracy over a simple autoregressive benchmark (with constant parameters and variance) but that it was difficult to beat a VAR (with constant parameters and covariance matrix) estimated on a rolling sample. Aastveit et al (2017) estimated models of various dimensions using US data but focused on the evaluation of the forecast accuracy with respect to GDP growth, unemployment rate and inflation. They found that the model with time-varying parameters and stochastic volatility had difficulties outperforming a model with constant parameters and covariance matrix.…”
Section: Out-of-sample Forecastsmentioning
confidence: 99%
“…This shift in the parameters' signal we find after the crisis is also consistent with recent empirical evidence in VAR models and evaluation of shock transmission (Aastveit, Carriero, Clark, & Marcellino, ).…”
supporting
confidence: 91%
“…Banbura, Giannone, and Reichlin (2010) show that large VARs containing more than 100 variables can work effectively, a finding that has contributed to a resurgence in the use of VARs in forecasting and policy analysis by both central banks and private forecasters. 1 In this paper, we propose a technique to adjust the medium-term and long-horizon forecasts from a VAR toward plausible values proposed by judgmental forecasters. Specifically, we utilize the technique of relative entropy to alter the medium-term to longhorizon VAR forecast to match that of the real-time survey long-horizon forecast.…”
Section: Introductionmentioning
confidence: 99%